Wind action on steel chimneys according to standards - Lipecki, Tomasz; Bęc, Jarosław; Jamińska, Paulina (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Analysis of the steel chimneys response to the wind action has been presented in the paper. The approaches presented in the Polish standards: referring to the steel chimneys [1] and to the wind action [2], as well as in the Eurocode 1 [3] have been shown here. The comparisons of the inline wind action according to these procedures, as well as in the cross-wind directions have been made. The responses to the wind action, i.e. displacements at the top of each chimney, have been compared as well. The real chimneys have been subjected to the analyses. Almost each of them had collapsed, mainly because of the vortex excitation. All chimneys and wind actions have been modelled by FEM system – Autodesk Mechanical Simulation 2013.